Delivery of Distance Counselling to Survivors of Sexual Violence: A Scoping Review of Promising and Best Practices - Janette Leroux PhD; Natalie Johnston MPH; Ashley-Anne Brown BScH; Alanna Mihic MSc; Denise DuBois PhD; AnnaLise Trudell PhD (SAGE Publishing, 2022)
Distance counselling holds immense potential for improving access to trauma supports for survivors of sexual violence (SV), and particularly for under-served groups who disproportionately experience violence and myriad barriers to accessing in-person supports. And yet, the evidence-base for the practice and delivery of distance counselling remains under-developed. In the context of COVID-19, where telehealth applications have undergone a rapid uptake, we undertook a scoping review of existing evidence of therapeutic and organizational practices related to the real-time (synchronous) delivery of distance counselling to survivors of SV. We based our scoping review methods on Arksey and O'Malley framework and in accordance with the guidance on scoping reviews from the Joanna Briggs Institute (JBI) and PRISMA reporting guidelines for scoping reviews. A comprehensive search of MEDLINE, Embase, PsycINFO, CINAHL, Web of Science, and Sociological Abstracts was undertaken in October 2020, and again in March 2022. Searching, reviewing, appraisal, and data extraction was undertaken by two reviewers. In total, 1094 records were identified that resulted in 20 studies included. Descriptions, findings, and recommendations were gleaned and synthesized into potential practices using inductive thematic analysis. While many studies have an appreciative orientation to distance counselling, these benefits tend to be framed as non-universal, and conditional on survivor safety, flexibility, anonymity, survivor choice, strong and inclusive technology, and a supported workforce. Despite the limited evidence-base, we present several clusters of findings that, taken together, can be used to support current COVID-19 distance counselling initiatives with survivors, as well as guide the future development of best practices.